Undetermined noun phrases in New Englishes: zero or null article? - Abdul Wahid, Mohd Ridwan (2014)
This corpus-based study investigates the phenomenon of article omission in Singapore English, Indian English and Kenyan English using a case study of noun phrases headed by ‘house’. Data from British English, Australian English and New Zealand English are used for comparative purposes. The paper will show that conceiving Ø as the null article, rather than its zero counterpart, can throw light on New English speakers’ intended meanings of those undetermined noun phrases that are often explained away as cases of article omission. Undetermined noun phrases headed by ‘house’ are indeed more frequent in New Englishes but about 80% of them are instantiations of the null article which is also found to be common in the native varieties, as can be seen in, e.g., ‘We are moving Ø house’ or ‘You set up Ø house together’. Interpreted with the null article, many of the otherwise untypical noun phrases in the newer varieties become identifiable, inclusive and maximally abstract (Chesterman 2005). Some 15% of the investigated noun phrases are one-member sets which also act as proper names e.g., ‘House’ for ‘The House of Representatives’. Finally, ‘house’ is found to be used in the phrase ‘in Ø house’ by way of misanalysis. This is due to ‘house’ in the adjectival compound ‘in + house’ being treated as an overt noun. Broadened in its scope of description, the phrase is consequently used as a premodifier or a postmodifier. With this re-interpretation the incidence of ungrammaticality is low, thus shedding light on the widespread occurrence of article omission in the New Englishes.